2015
DOI: 10.3758/s13414-015-0882-9
|View full text |Cite
|
Sign up to set email alerts
|

The cocktail-party problem revisited: early processing and selection of multi-talker speech

Abstract: How do we recognize what one person is saying when others are speaking at the same time? This review summarizes widespread research in psychoacoustics, auditory scene analysis, and attention, all dealing with early processing and selection of speech, which has been stimulated by this question. Important effects occurring at the peripheral and brainstem levels are mutual masking of sounds and “unmasking” resulting from binaural listening. Psychoacoustic models have been developed that can predict these effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
307
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(327 citation statements)
references
References 141 publications
12
307
2
6
Order By: Relevance
“…This cue then indicates which task participants should perform in the upcoming trial. This kind of explicit cueing-procedure has been used in several studies to investigate auditory selective attention in a dichotic listening paradigm , 2015Koch, Lawo, Fels, & Vorländer, 2011;, 2015Lawo, Fels, Oberem, & Koch, 2014). In the dichotic listening paradigm, two different auditory stimuli or auditory streams are presented simultaneously, one to each ear.…”
Section: Intentional Control Of Auditory Attention In Selective Listementioning
confidence: 99%
See 2 more Smart Citations
“…This cue then indicates which task participants should perform in the upcoming trial. This kind of explicit cueing-procedure has been used in several studies to investigate auditory selective attention in a dichotic listening paradigm , 2015Koch, Lawo, Fels, & Vorländer, 2011;, 2015Lawo, Fels, Oberem, & Koch, 2014). In the dichotic listening paradigm, two different auditory stimuli or auditory streams are presented simultaneously, one to each ear.…”
Section: Intentional Control Of Auditory Attention In Selective Listementioning
confidence: 99%
“…Typically, participants only attend to one ear. Auditory selective attention allows the listener to focus on the relevant auditory stimulus, while distracting stimuli remain in the perceptual background (for reviews, see Bronkhorst, 2015;Lachter, Forster, & Ruthruff, 2004;Schneider, Li, & Daneman, 2007;Shinn-Cunningham, 2008). Early studies on auditory selective attention in a setting with competing stimulus streams have focused on sustained auditory attention and involuntary attention capture (for early examples of dichotic listening, see Broadbent, 1958;Cherry, 1953; for a review see Hugdahl, 2011, for studies on selective attention to a certain part of a complex stimulus, see Mondor, & Bregman, 1994;Mondor, Zatorre, & Terrio, 1998).…”
Section: Intentional Control Of Auditory Attention In Selective Listementioning
confidence: 99%
See 1 more Smart Citation
“…Traditional models that predict SRM based on interaural differences in level (ILDs) and time (ITDs) are generally successful in predicting the intelligibility of target speech when target and maskers are spatially separated in the azimuthal plane (Zurek, 1993;Bronkhorst, 2015). Recent studies of speech-on-speech masking have concluded that SRM is a combination of better-ear listening and binaural analysis (Kidd et al, 1998;Freyman et al, 1999;Arbogast et al, 2002;Best et al, 2006;Marrone et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Преимущества бинаурального слуха обеспечивают-ся сложными нейрофизиологическими процессами [18]. Точная локализация в пространстве источника звука [13] и лучшая разборчивость речи при наличии шума возмож-ны благодаря трем компонентам бинаурального слуха: эффекту «тени головы», эффекту бинаурального шумопо-давления и эффекту суммации [19].…”
Section: Discussionunclassified